A Novel Fuzzy Based Single Switch Converter For High Speed Srm Drive Applications (International Journal of Engineering and Computer Science, 2015)
The design of the fuzzy logic controller is the voltage control action as feedback for significantly improving the dynamic performance of converter. The switches pertaining in Switched reluctance motor (SRM) drive is receiving increasing attentions from various researchers as well as viable candidate for adjustable speed and servo applications. Switched Reluctance Motors have a simple structure and inherent mechanical strength without rotor winding. A new converter for SRM which uses only one switch per phase consisting an important characteristic “fast phase current commutation” is used to improve dynamic performance, Speed Range and efficiency. Recently, the demand of high speed drives has been increased due to its mechanical advantages. High speed drive systems are widely used in the industrial applications such as blowers, compressors, pumps and spindles due to the compact size and high efficiency. This paper presents a new fuzzy controller design for a switched reluctance motor drive system. The simulation results based on Matlab/Simulink are discussed in detail.